DESIGNING ENGLISH SYLLABUS FOR KINDERGARTEN AT TK NISRINA BEKASI - Ika Chairiyani; Rahmat (Dialectical Literature and Educational Journal, 2020)
The current trends show that the teaching of English is not only conducted in elementary schools but also in kindergartens. The research was initiated by the fact that English has been included as a program in kindergarten. However, that program is not supported by the availability of qualified teachers and English syllabus.This study is focused on developing English syllabus for Kindergarten in TK Nisrina Bekasi. It tries to answer the research problem about how to develop English syllabus which covers the learning objectives which meet the students' needs, the materials which provide successful achievement, and the teaching methods which guide teachers how the materials are to be taught, and the evaluation which assesses how far the learning objectives are reached. This is a Research and Development study conducted in two activities; needs analysis, and syllabus development based on the information from needs aanalysis. The syllabus is developed based on the curriculum which is made after carrying out the need analysis. The draft of the syllabus was evaluated by two experts and the feedbacks were used to revise the draft. Field try-out was conducted to get feedbacks used to revise the draft. The final revision is the Final Product. The instruments used to collect the data were questionnaires, observation, and interview.The results of needs analysis showed that the teachers got confused to formulate learning objectives. They also had difficulties to find the materials for several themes and sub-themes and they only applied a few teaching techniques and very limited media. This occurs because there is no curriculum for teaching English in kindergarten. Therefore, from the data, the first draft of syllabus was made. Then it was revised after obtaining the feedback from the experts.